Значение переводных письменныx памятников для становления анатомической науки в России - Ушинскене, Виктория (Kalbotyra, 1997)
The article is devoted to the role of foreign written sources in the process of the development of anatomical knowledge in Russia. Natural economy, human medicine and cooking formed some notions of the appearance of principle body orifices and organs appearance and shape, but they did not permit the understanding of the peculiarities of organ functions and physiology. The situation changed after Russia was Christianized and treatises of European scientists began to available in the country. In the article the main patterns of this kind of literature translated into Old Russian are presented.